Geofluid mapping reveals the connection between magmas, fluids, and earthquakes - Hikaru Iwamori; Yasuo Ogawa; Tomomi Okada; Tohru Watanabe; Hitomi Nakamura; Tatsu Kuwatani; Kenji Nagata; Atsushi Suzuki; Masahiro Ichiki (Communications Earth & Environment)
Abstract Subsurface geofluids drive Earth’s evolution through seismogenesis, volcanism, and plate motion. Previous geofluid-distribution estimates from various geophysical methods show large variations. To quantify the geofluid distribution, we employ a novel inversion method capable of simultaneously analysing seismic velocity from high-resolution seismic-wave tomography along with electrical conductivity from magnetotelluric data in a volcanic region of Northeast Japan. This study successfully maps the volume and geometrical parameters of aqueous fluids and basaltic and andesitic magmas. A large, slightly leaking fluid reservoir is identified at a depth of 10–20 km. The fluid pressure-depth profile indicates that the seismogenic region corresponds to the area with the highest excess fluid pressure directly above the reservoir. At the bottom of the reservoir near the Moho, the basaltic and andesitic magmatic roots exhibit horizontal distributions to the west and east of the volcanic front, respectively. Andesitic magma is identified directly beneath the front, along with a magma-depleted zone near the Moho. We deduce that magma along the Moho released aqueous fluids, resulting in high pore-fluid pressure that induced earthquakes in the upper crust. Certain magmas ascended to form active volcanoes, leaving behind a magma-depleted zone. Our findings highlight the importance of crustal processes in volcanic-front formation.